Earthquake-induced impulsive release of water in the fractured aquifer system: Insights from the long-term hydrochemical monitoring of hot springs in the Southeast Tibetan Plateau. (January 2023) - Tian, Jiao; Zhou, Xiaocheng; Yan, Yucong; He, Miao; Li, Jingchao; Dong, Jinyuan; Liu, Fengli; Ouyang, Shupei; Li, Ying; Tian, Lei; Wang, Yingchun; Huang, Tianming; et al.
Abstract: The outpouring hot spring water is deep circulated groundwater and its chemical constituents act as information carriers of the hydrological setting, including the recharge source, circulation path, and reservoir properties. However, the temporal variation in hydrochemical components and their inducing mechanisms remain to be elucidated. In this study, hot springs along the Anninghe-Zemuhe Fault, a controlling fault on the eastern edge of the Tibetan Plateau, were investigated. According to the spatial chemical variations of the sixteen hot springs and the two-year hydrochemical monitoring results of four hot springs, the aquifers in such fault-controlled regions exhibit heterogeneous anisotropy and elastic properties. Earthquake activities were found to play a significant role in both spatial and temporal changes in chemical compositions. We found that the waters with the highest reservoir temperatures (∼100 °C) and deepest circulation depth (∼3 km) outcropped in the north of the fault, where earthquakes occur more intensively, deeply, and stronger than those in other parts of the fault. During the stress accumulating and releasing processes in the earthquake sequence, the fractured aquifer systems are elastic and subject to impulsive mixing with subordinate fracture waters which induced hydrochemical changes at different levels. The chemical constituents responded to seismic energy densities as low as 6.5 × 10 −4  J/m 3, showing superiority over the groundwater monitoring wells. However, earthquakes that occurred in a tectonically independent area or with an inappropriate stress loading-unloading direction could fail to trigger a distinguishable mixing process with apparent chemical fluctuations. These findings provide insights into the hydrochemical response to earthquakes in orogenic areas and further draw attention to hydrochemical changes in hot spring waters in seismic studies. Highlights: Hot spring waters circulate deeply where earthquakes occurred intensively. Fractured aquifers in orogenic regions are elastic, heterogeneous, and anisotropic. 3D analysis of the temporal chemical change uncovers the impulsive mixing process. Mixing with subordinate fracture waters is triggered during the earthquake cycle.